1992
DOI: 10.1002/1097-0142(19920815)70:4<854::aid-cncr2820700422>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the recruitment of macrophages to cancer site. In vivo concentration gradient of monocyte chemotactic activity

Abstract: Background. Tumor stroma is characterized by the development of new blood vessels, a n inflammatory cell infiltration, and a fibrotic reaction. The inflammatory component of tumor stroma plays an important role in the modulation of tumor expansion. In this respect, macrophages constitute a major part of the inflammatory cell infiltration and can exert cytotoxic activity against tumor cells. The accumulation of macrophages in the vicinity of the tumor suggests their recruitment from circulating blood monocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The interstitial pH within solid tumors has been observed to be below physiological levels, ranging from 5.6 -7.7, which includes the pH optimum of FcRn binding (50). Macrophages are recruited in the earliest phases of inflammation such as inflammatory bowel disease (52), and they are widely infiltrated in solid tumor tissues (53).…”
Section: Discussionmentioning
confidence: 99%
“…The interstitial pH within solid tumors has been observed to be below physiological levels, ranging from 5.6 -7.7, which includes the pH optimum of FcRn binding (50). Macrophages are recruited in the earliest phases of inflammation such as inflammatory bowel disease (52), and they are widely infiltrated in solid tumor tissues (53).…”
Section: Discussionmentioning
confidence: 99%
“…A dynamic relationship forms between the pre-neoplastic/ neoplastic and non-neoplastic stromal cell populations through stromagen and gliomagens release, which together facilitate tumorigenesis, tumor maintenance and glioma progression. endothelial growth factor (Forstreuter et al, 2002;Kerber et al, 2008), hepatocyte growth factor (Badie et al, 1999;Kunkel et al, 2001), monocyte chemoattractant protein-1 (Martinet et al, 1992;Leung et al, 1997) and the chemokine CX3CL1 (fractalkine) through activation of the CX3CR1 receptor (Held-Feindt et al, 2010). Monocyte chemoattractant protein-1 can also increase the surface expression of CX3CR1 on microglia (Green et al, 2006), thus providing amplification circuits for further microglia recruitment.…”
Section: Stromal Determinants Of Glioma Formation and Growthmentioning
confidence: 99%
“…M1 Mº are powerful immune effector cells characterized by a high ability to present antigens and to produce proinflammatory cytokines and toxic intermediates, while M2 Mº display a poor antigen-presenting capacity and are polarized to release many different immunosuppressive molecules as well as to promote angiogenesis and extracellular matrix degradation (6)(7)(8)(9). It has been indicated that TAMs, which derive almost entirely from circulating monocytes (Mo) recruited and differentiated in the tumor milieu (10)(11)(12), often display phenotypic features consistent with those of M2 Mº and, accordingly, can actively sustain tumor growth and contribute to generate an immunosuppressive microenvironment (7,13). Moreover, recent evidence demonstrated the existence of Mo with M2-like phenotypes, which could thus be a preferential source of M2 Mº and important players in tumor-induced immunosuppression (10,12 The definition of the role of individual immune cell types on the outcome of the anti-tumor immune responses is of pivotal importance for the rational design of new antineoplastic immunotherapy approaches.…”
Section: Introductionmentioning
confidence: 99%
“…It has been indicated that TAMs, which derive almost entirely from circulating monocytes (Mo) recruited and differentiated in the tumor milieu (10)(11)(12), often display phenotypic features consistent with those of M2 Mº and, accordingly, can actively sustain tumor growth and contribute to generate an immunosuppressive microenvironment (7,13). Moreover, recent evidence demonstrated the existence of Mo with M2-like phenotypes, which could thus be a preferential source of M2 Mº and important players in tumor-induced immunosuppression (10,12 The definition of the role of individual immune cell types on the outcome of the anti-tumor immune responses is of pivotal importance for the rational design of new antineoplastic immunotherapy approaches. In this respect, however, the functional role of the leukocytes infiltrating MM tissues is still poorly defined (4).…”
Section: Introductionmentioning
confidence: 99%